2020
DOI: 10.18043/ncm.81.6.377
|View full text |Cite
|
Sign up to set email alerts
|

10 Years Later : The Impact of the Affordable Care Act on Prevention and Public Health in North Carolina

Abstract: The passage of the Affordable Care Act had a great impact on the landscape of public health programming and clinical preventive care in North Carolina. Large funding measures have supported community-based prevention efforts and led to policy, systems, and environmental changes to support a healthier population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…44,45 Ninety-eight of 100 North Carolina counties fund disease prevention. 9 Indicative of gaps in North Carolina LHD resources, a 2018 study 41 found that only 4% of responding LHDs prescribed preexposure prophylaxis (PrEP); just 13% of LHDs refer for PrEP. The reasons for not offering PrEP included not seeing LHD clients as at risk for HIV.…”
Section: Lhdsmentioning
confidence: 99%
See 2 more Smart Citations
“…44,45 Ninety-eight of 100 North Carolina counties fund disease prevention. 9 Indicative of gaps in North Carolina LHD resources, a 2018 study 41 found that only 4% of responding LHDs prescribed preexposure prophylaxis (PrEP); just 13% of LHDs refer for PrEP. The reasons for not offering PrEP included not seeing LHD clients as at risk for HIV.…”
Section: Lhdsmentioning
confidence: 99%
“…More than 60 years later, LHDs continue to be critical to southern prevention efforts 44,45 . Ninety-eight of 100 North Carolina counties fund disease prevention 9 . Indicative of gaps in North Carolina LHD resources, a 2018 study 41 found that only 4% of responding LHDs prescribed preexposure prophylaxis (PrEP); just 13% of LHDs refer for PrEP.…”
Section: Lhdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the most expansive work in this area in North Carolina occurred under the Communities Putting Prevention to Work and Community Transformation Grants, which the Centers for Disease Control and Prevention (CDC) established to focus on tobacco, active living, and healthy eating. Through this fund-ing, the North Carolina Division of Public Health and local health departments across the state supported the implementation of an estimated 200 policy and environmental changes to reinforce healthy living, including smoke-free air policies, joint-use agreements for school playgrounds, and healthy food retail changes [4]. This work continues today through the Healthy Communities program.…”
Section: Introductionmentioning
confidence: 99%